Rate of force development and time to peak force during plyometric exercises - Jensen, R. L.; Flanagan, E. P.; Ebben, W. P. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Rate of force development (RFD) during the first 100 and 250 msec of the positive acceleration phase of plyometric exercises and time to peak force were determined in 23 NCAA Div. I athletes. Subjects performed a countermovement jump (CMJ), cone hop (CH), tuck jump (TJ), single leg CMJ (SLJ), and squat jump with 30% 1 RM squat (SJ30) on a force platform. Results showed SLJ and SJ30 had lower RFD100 and higher time to peak force, while CH and TJ had higher RFD100 and shorter time to peak force (p<0.05). These findings are in agreement with previous research that shows that quick movement exercises have high RFD. However, RFD250 may be an inappropriate measure to classify very quick jumps, such as the CH, because RFD values approach zero or become negative when subjects are close to or already leaving the ground.